Fractional flow reserve use during elective coronary angiography among elderly patients in the US. (March 2019) - Kay, Bradley; Joseph, Timothy A.; Lehrich, Jessica L.; Curzen, Nick; Nallamothu, Brahmajee K.
Abstract: Fractional flow reserve (FFR) is a physiologic measurement of coronary artery perfusion. Studies have demonstrated its benefit in lowering cost and improving outcomes in patients undergoing elective coronary angiography, though follow-up surveys have demonstrated low usage nationwide. We sought to investigate the actual usage in elderly patients undergoing elective coronary angiography. Overall utilization of FFR for elective coronary angiography was 6.3%. Age, sex, race, prior stress testing and region of the country were all statistically significant predictors for FFR use. There still exist many barriers to widespread adoption of this modality, which require further exploration.